Deep lie a novel - Woods, Stuart (New York : Harper Paperbacks, 1986)
Based on the Soviet submarine sightings along the Swedish coast, this espionage thriller focuses on the struggle between a KGB genius and a CIA analyst.
Keywords: United States. -- Central Intelligence Agency -- Fiction; Submarines (Ships) -- Fiction